A study of the breeding biology of a pied flycatcher population in Wales - Hesp, Jon (1993)
This study concerns a population of the Pied Flycatcher (Ficedula hypoleuca) living in nestboxes in an area of woodland in Mid-Wales. The occupants of 180 nestboxes were monitored during 1988 and 1989. In addition to behavioural observations and records of breeding performance, individual adults and pulli were caught and measured, and a blood sample taken. In the Pied Flycatcher, polygyny is a common mating strategy in which the two or more females mated to a single male nest in discrete territories up to 500m apart This behaviour has been interpreted in two ways, firstly as the result of female choice for the quality of the male or his territory, and secondly, as a consequence of male deception, by which already-mated males attract secondary females who suffer reduced breeding success as a result. In this population polygyny was a rare occurrence; only 3 of 240 breeding males were recognised to be polygynous. These males defended two adjacent nestboxes. The breeding success of the three secondary females was not unusually low. These results suggest that a model of male- or territory quality might better explain the situation in this population. The occurrence of extra-pair mating has being noted in a number of species, including the Pied Flycatcher. In this study it was found to account for 2.7% of the offspring screened by genetic fingerprinting. Another common method for detecting extra-pair paternity uses the heritability of a skeletal measurement.The results from the two methods are shown to be incompatible. A number of weaknesses with the heritability method are described and discussed. The increasing number of studies on the Pied Flycatcher throughout Europe reveal that the frequency of mating strategies such as polygyny and extra-pair mating differ from area to area This suggests that environmental factors may play a major part in determining the costs and benefits of such strategies.